EFISIENSI TEKNIS USAHATANI JAGUNG DI DESA SUKA PINDAH - Utama, Satria Putra (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2004)
The general objective of the study was to estimate technical efficiency of farmers under Bengkulu Regional Development Project (BRDP) through Unit Pengelola Keuangan Desa (UPKD) of com farmers' practice in Suka Pindah, Lubuk Pinang Sub-district, Bengkulu Province. Suka Pindah was choosen by purposive method because this area one of the production center for com in Bengkulu Province. The research was conducted on December 2003, using a total of 30 respondents chosen by simple random sampling from 138 farmers. The stochastic frontier production function estimation using MLE showed that seed and labour had positive significant influence on the value of the output. Nitrogen (urea) coefficient had negative sign but this was not Significant. SP36, KGf, Herbidde and UPKD had positive sign, but these were not significant. The average of technical efficiency was 70 % for the com farmers'in Suka Pindah, it's mean that there is chance to increase the effiCiency around 30 % more compare to the best farmers' practices.